Meta-analysis of association between atmospheric ozone exposure and atherosclerotic cardiovascular disease - Bingqian WANG; Teng YANG; Shuting XIE; Meng TAN; Guoxing LI; Jing HUANG (环境与职业医学, 2025)
BackgroundAtherosclerotic cardiovascular disease (ASCVD) is a major contributor to the global burden of cardiovascular diseases. However, evidence from meta-analyses on the association between ambient ozone exposure and ASCVD risk remains relatively insufficient. ObjectiveTo explore the epidemiological association between ambient ozone exposure and ASCVD, providing scientific evidence for ASCVD prevention and control from the perspective of environmental risk factor management. MethodsWe systematically searched PubMed, Web of Science, Embase, the Cochrane Library, CNKI, Wanfang Database, CBM, and VIP for published epidemiological studies on the relationship between ambient ozone exposure and ASCVD from January 2007 to December 2023. We performed quality assessment and data extraction of the included studies, and utilized meta-analysis to evaluate the effects of short-term and long-term ozone exposure on different ASCVD outcomes, including mortality and incidence of ischemic heart disease (IHD) and ischemic stroke (IS). ResultsA total of 24 studies were included based on a set of predetermined eligibility criteria. The meta-analysis results indicated that short-term ozone exposure was associated with an increased risk of ASCVD mortality and incidence. Specifically, short-term ozone exposure was significantly associated with an elevated risk of IHD mortality (combined RR=1.011, 95%CI: 1.008, 1.015; P < 0.05). Additionally, short-term ozone exposure was significantly linked to increased IS mortality (combined RR=1.005, 95%CI: 1.003, 1.008; P < 0.05) and incidence (combined RR=1.015, 95%CI: 1.003, 1.027; P < 0.05). ConclusionShort-term exposure to ambient ozone significantly elevates acute cardiovascular disease risk. However, the epidemiological association between long-term ozone exposure and ASCVD remains inconclusive. Future high-quality cohort studies with refined exposure assessment methods are warranted to elucidate the chronic cardiovascular effects of ozone exposure.